-2x-7(-2x-23)=77

Simple and best practice solution for -2x-7(-2x-23)=77 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-7(-2x-23)=77 equation:



-2x-7(-2x-23)=77
We move all terms to the left:
-2x-7(-2x-23)-(77)=0
We multiply parentheses
-2x+14x+161-77=0
We add all the numbers together, and all the variables
12x+84=0
We move all terms containing x to the left, all other terms to the right
12x=-84
x=-84/12
x=-7

See similar equations:

| 3/2(d+12)=1/2(2d+-6) | | 3a–5(a–2)=34 | | 3x–(x–x)=x+4 | | 6.2-x=8.x | | 2x+7=-5x+3 | | ​3​​2​​b+5=20−b | | 5=x+45/8 | | 6=a-2.5 | | 6=-3/7x | | x+1/2x+3=180 | | 7a=56+a | | -12/5=-6x | | 2.x-8=10-3.x+2 | | 4(a=3)=12+4a | | |3x+5|=9 | | 13=7-3w | | 1,5x+0,8=1,4 | | 33x-11=24x+8+71 | | 4(3x-5)=6(2x-3) | | 6(x-7)-4(x=3)=-1 | | -11=7x+2/3 | | -5/8u=-35 | | 7x+6(x-4)=15 | | 3.x-2=2.x+5 | | ​h/6​​−1=3 | | 3^x*3^(x+1)=3 | | 5x2+28x−12=0 | | -27=6x+3 | | ​h6​​−1=3 | | x-5/8=3/16 | | 7x+6x-24=15 | | 4+3x=7x-4 |

Equations solver categories